2010
DOI: 10.4103/0970-1591.74462
|View full text |Cite
|
Sign up to set email alerts
|

Management of ureteric stone in pediatric patients

Abstract: The management of ureteral stones in children is becoming more similar to that in adults. A number of factors must be taken into account when selecting one's choice of therapy for ureteral stone in children such as the size of the stone, its location, its composition, and urinary tract anatomy. Endoscopic lithotripsy in children has gradually become a major technique for the treatment of ureteral stones. The stone-free rate following urteroscopic lithotripsy for ureteral stones has been reported in as high as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…If ESWL is not promising, ureteroscopy can be used [35,36]. The increasing availability of smaller size endourological equipment has made it possible to manage paediatric ureteral stones using endoscopic techniques [37][38][39][40][41]. The technique used in children is similar to that used in adults.…”
Section: Ureteroscopymentioning
confidence: 98%
See 1 more Smart Citation
“…If ESWL is not promising, ureteroscopy can be used [35,36]. The increasing availability of smaller size endourological equipment has made it possible to manage paediatric ureteral stones using endoscopic techniques [37][38][39][40][41]. The technique used in children is similar to that used in adults.…”
Section: Ureteroscopymentioning
confidence: 98%
“…Because of the smaller size of the probes, laser energy is easier to use in smaller instruments and is more useful for paediatric cases. All studies reporting the use of endoscopy for ureteric stones in children have clearly demonstrated that there is no significant risk of ureteric strictures or reflux with this mode of therapy [39][40][41].…”
Section: Ureteroscopymentioning
confidence: 98%
“…Some cases require more than 1 session of ESWL (up to 3 sessions) for a better stone-free rate (1,2,8,9). Each session consists of 1800 to 2000 shock waves (and up to 4000) between 14 and 21 kV (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of ESWL is measured by the stonefree rate, which has been reported from 50% to 95% in children (1)(2)(3)8). Some cases require more than 1 session of ESWL (up to 3 sessions) for a better stone-free rate (1,2,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of a calculus in the ureter, the question to be answered is whether the stone will pass spontaneously or not. In general, the rate of spontaneous passage of a stone less than 4mm is related to its position in the ureter, 75% in the distal, 60% in the middle and 50% in the proximal ureter 14 . On the other hand, stones of 5mm-10mm have a spontaneous passage rate of 10 -50% depending on the position at which they are located.…”
Section: +964750771476mentioning
confidence: 99%